1991
DOI: 10.1007/bf01045047
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of bone sialoprotein in foetal porcine bone tissues: comparisons with secreted phosphoprotein 1 (SPP-1, osteopontin) and SPARC (osteonectin)

Abstract: Bone sialoprotein (BSP) is a prominent component of bone tissues that is expressed by differentiated osteoblastic cells. Affinity-purified antibodies to BSP were prepared and used in combination with biotin-conjugated peroxidase-labeled second antibodies to demonstrate the distribution of this protein in sections of demineralized foetal porcine tibia and calvarial bone. Staining for BSP was observed in the matrix of mineralized bone and also in the mineralized cartilage and associated cells of the epiphysis, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(55 citation statements)
references
References 39 publications
4
50
0
1
Order By: Relevance
“…In the current experiments, new bone formation by osteoblastic mesenchymal cells was already observed at 4 days post-operation, and many bone trabeculae were produced within injured medullary cavities at 7 days post-operation. BSP is a non-collagenous bone matrix protein and is localized at the calcification sites of developing bone (Bianco et al, 1993;Chen et al, 1991). Although the expression of BSP at 7 and 14 days post-operation was relatively weak in newly-formed tra- becular bone matrix, there was no difference in intensity of BSP expression between EMD-and PGA-applied femurs.…”
Section: Discussionmentioning
confidence: 83%
“…In the current experiments, new bone formation by osteoblastic mesenchymal cells was already observed at 4 days post-operation, and many bone trabeculae were produced within injured medullary cavities at 7 days post-operation. BSP is a non-collagenous bone matrix protein and is localized at the calcification sites of developing bone (Bianco et al, 1993;Chen et al, 1991). Although the expression of BSP at 7 and 14 days post-operation was relatively weak in newly-formed tra- becular bone matrix, there was no difference in intensity of BSP expression between EMD-and PGA-applied femurs.…”
Section: Discussionmentioning
confidence: 83%
“…For example, this analysis of primitive progenitor cells revealed a small group of colonies expressing low but detectable levels of BSP; a few of these colonies also expressed COLL-I, but no other osteoblast-associated molecules. We (Liu et al, 1994) and others (Bianco et al, 1991;Bianco et al, 1993;Chen et al, 1991) have shown that BSP is upregulated as osteoblasts mature in vitro and in vivo at sites of de novo bone formation. While it is generally considered a relatively late stage marker, expressed concomitantly with OCN and just prior to mineralization, where it has been proposed to seed hydroxyapatite crystal formation (Hunter and Goldberg, 1993), we have established that it is upregulated prior to OCN and well before detectable mineralization can be observed (Liu et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The prominence of osteopontin in bone matrix and the regulation of its expression by osteotropic hormones have focused attention on the role of this protein in bone development and remodeling (Prince and Butler, 1987;Yoon et al, 1987;Kubota et al, 1989;Noda et al, 1990;Reinholt et al, 1990;Chen et al, 1991;Moore et al, 1991). However, several laboratories have shown that osteopontin mRNA is expressed by a number of tissues, including kidney, ovary, uterus, and others (Yoon et al, 1987;Nomura et al, 1988;Denhardt et al, 1989;Young et al, 1990;Craig and Denhardt, 1991).…”
Section: Introductionmentioning
confidence: 99%